2009
DOI: 10.3102/0034654309332561
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Book Reading in Early Education: A Tool to Stimulate Print Knowledge as Well as Oral Language

Abstract: This meta-analysis examines to what extent interactive storybook reading stimulates two pillars of learning to read: vocabulary and print knowledge. The authors quantitatively reviewed 31 (quasi) experiments (n = 2,049 children) in which educators were trained to encourage children to be actively involved before, during, and after joint book reading. A moderate effect size was found for oral language skills, implying that both quality of book reading in classrooms and frequency are important. Although teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
319
0
21

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(357 citation statements)
references
References 73 publications
17
319
0
21
Order By: Relevance
“…An interesting question is whether the same effects would be expected if this EF approach was adopted by parents or educators, given evidence from a recent meta-analysis suggesting that many researcher-generated effects were not replicable when implemented by non-researchers (Mol, Bus, & De Jong, 2009). Unique to the current series of studies is our adoption of a different fieldworker for each study, all of whom had experience in early childhood education and care contexts (with two of the three having experience as preschool educators).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting question is whether the same effects would be expected if this EF approach was adopted by parents or educators, given evidence from a recent meta-analysis suggesting that many researcher-generated effects were not replicable when implemented by non-researchers (Mol, Bus, & De Jong, 2009). Unique to the current series of studies is our adoption of a different fieldworker for each study, all of whom had experience in early childhood education and care contexts (with two of the three having experience as preschool educators).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent meta-analysis (Mol et al, 2009) has confirmed that interactions between parents and children focused upon books and stories appear to be a key stimulus for children's vocabulary development and their knowledge of print and its conventions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to read does, of course, make many high cognitive demands and there has been considerable debate about the most suitable age at which to begin formal instruction in this skill. With children aged 0 to 4 years, the emphasis has tended to be on developing their attitudes towards reading rather than their skills in performing it (Wade & Moore, 2000;Hines & Brooks, 2005;Mol et al, 2009). Programmes designed to develop children's relationships with reading, and with books, have proved quite popular.…”
Section: Exploring a National Book-gifting Scheme: Parents' And Childmentioning
confidence: 99%
“…Research has indicated that explicit instruction on target words in meaningful dialogues involving defining and embedding words in a meaningful context yields higher word learning rates than implicit instruction through fast mapping (i.e., mapping of a word label on its referent after only one exposure) or extracting meaning from multiple uses of a word in context as the basic word learning mechanisms [48,51]. Therefore, for the L2TOR project, an overall theme for the lessons was selected that would be familiar and appealing to most children, and, as such, increase childrens engagement during the tutoring sessions.…”
Section: Meaningful Interactionmentioning
confidence: 99%